The Differentiation Principle: Why Consumers Often Neglect Positive Attributes of Novel Food Products - Florack, Arnd; Koch, Teresa; Haasova, Simona; Kunz, Sonja; Alves, Hans (Journal of Consumer Psychology, 2021)
To address the growing health awareness of consumers, the food industry designs novel food alternatives, which are similar but not identical to existing foods (e.g., meat‐reduced or plant‐based burgers). The idea is that consumers can continue to eat their preferred kind of food and still follow a healthy diet. However, we argue that it is too short‐sighted to hope that positive similarities to existing products help to increase purchase intentions, because consumers often focus on distinct attributes of new products and neglect the positive attributes shared by existing and novel food alternatives. We tested our hypotheses in six studies in which participants provided or received attributes for classic food products and novel alternatives with substituted ingredients to make them healthier. We observed that consumers perceive the distinguishing attributes between a classic product and its novel, healthier alternative to be predominantly negative, whereas they perceive most shared attributes to be positive. Moreover, we found the predicted neglect of shared attributes in the formation of taste expectations and purchase intentions. In the conclusion, we put forward that the observed evaluation bias can impede the success of novel food alternatives and discuss possible ways to overcome this disadvantage.